Fuch's heterochromic iridocyclitis in Ibadan (1995)
An uncommon form of uveitis, Fuch's heterochromic iridocyclitis is presented in 8 patients seen at the eye clinic of the University College Hospital. The spectrum of the disease is discussed in the African eye.